RISK MANAGEMENT AS AN EFFECTIVE TOOL FOR INCREASING THE COMPETITIVENESS OF A BUSINESS ENTITY - TKACHENKO, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article deals with issues related to the analysis of financial and economic activities of an enterprise.  The methods for its realization are also investigated. Modern risks faced by business structures encourage the formation of effective management. Risk-oriented management should be viewed as a monolithic approach to understanding and predicting the likelihood of risks. Risk management is an effective tool for improving the competitiveness of a business entity. However, in order to detect certain changes in financial and economic results, effective control over the company's key financial indicators must be exercised. This results in the company's ability to implement measures aimed at protecting and enhancing the competitiveness of the business entity, its profitability, economic growth, efficiency of financial resources, solvency, use of labor and material resources, as well as the efficiency of the company as a whole. For a modern society, it is extremely important to form a clear vision of modern risks and their connection with the competitiveness of a business entity. This implies understanding the circumstances of the risk of minimizing it and identifying the consequences. Russia's armed aggression has created new threats and problems for the development of our country in general and its economy in particular. Without an efficiently functioning economy, it is impossible to win a war, so it is increasingly important to identify credible threats. Before establishing the probability of risks for a particular business entity, it is necessary to analyze the main financial indicators of its work. Based on the results obtained, the presence of dangers to the business environment of this entity is determined.  The most effective methods for determining the financial condition are the analysis of relative indicators and the DuPont method. Together, they provide a complete assessment of the enterprise's performance. Recommendations for analyzing the financial condition based on an integrated approach are substantiated.  Their expediency was confirmed in the calculations on the example of PJSC "Motor Sich".
Keywords: financial condition; enterprise; solvency; efficiency; R-analysis; Dupont method; financial indicators; stocks and costs; financial analysis